2017
DOI: 10.1002/2017gl074824
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Emission Within Jupiter's Main Auroral Oval

Abstract: We have discovered pulsating emission within Jupiter's main auroral oval, providing evidence of the auroral signature of Jovian ULF wave processes. The form comprises a 1° × 2° spot located directly on the main emission, whose intensity oscillates with a period of ∼10 min throughout the 45 min observation. The feature appears on the duskward edge of the discontinuity, maps to ∼13–14 h LT and ∼20–50 RJ, and rotates at around a half of rigid corotation. We show that the period of the oscillation is similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 35 publications
(59 reference statements)
2
38
1
Order By: Relevance
“…During this observation on 25 May (DOY145) 2017, the total flux of the UV aurora observed by Hisaki was ~1 TW, and the overall auroral activity was at a low level (see Figure 1 in Nichols, Badman, et al, ). We note that Nichols, Yeoman, et al () reported pulsating patches with ~11‐min periodicity in the UV images within the main oval region, while similar features could not be identified in the IR H 3 + aurora during this observation period. We could not perform any analysis in the active UV region, which is known to be variable and have periodic pulsations on timescales of 2–11 min (Bonfond et al, , ; Nichols, Badman, et al, ), because it was not possible to identify it due to the geometry of this observation.…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…During this observation on 25 May (DOY145) 2017, the total flux of the UV aurora observed by Hisaki was ~1 TW, and the overall auroral activity was at a low level (see Figure 1 in Nichols, Badman, et al, ). We note that Nichols, Yeoman, et al () reported pulsating patches with ~11‐min periodicity in the UV images within the main oval region, while similar features could not be identified in the IR H 3 + aurora during this observation period. We could not perform any analysis in the active UV region, which is known to be variable and have periodic pulsations on timescales of 2–11 min (Bonfond et al, , ; Nichols, Badman, et al, ), because it was not possible to identify it due to the geometry of this observation.…”
Section: Resultscontrasting
confidence: 40%
“…During this observation on 25 May (DOY145) 2017, the total flux of the UV aurora observed by Hisaki was~1 TW, and the overall auroral activity was at a low level (see Figure 1 in Nichols, Badman, et al, 2017). We note that Nichols, Yeoman, et al (2017) reported pulsating patches with~11-min periodicity in the UV images within the main oval region, while similar features could not be identified in the IR H 3 + aurora during this observation period.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Jupiter's enormous magnetosphere is capable of supporting waves of far lower frequency than the terrestrial magnetospheric ULF spectrum, and so the label ULF is often extended to <1 mHz. Observations span multiple data sets, most predominately X‐Ray, Infrared (IR), and Ultraviolet (UV) auroral emission modulations (Dunn et al, ; Gladstone et al, ; Nichols et al, ; Watanabe et al, ); magnetic perturbations (Khurana & Kivelson, ); radio emissions (Arkhypov & Rucker, ; Hospodarsky et al, ; Kimura et al, , ; MacDowall et al, ); and energetic particle flux modulations (Anagnostopoulos et al, ; Karanikola et al, ). The combined range of observed periods spans 1–100+ min, with several preferential 15‐, 30‐, and 40‐min periods referred to as QP15, QP30, and QP40, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Spacecraft such as Pioneer 10 and 11, Voyager 1 and 2, Ulysses, and Galileo have been used to identify a large number of similar QP wave periods of order ∼10-60 min. These pulsations are often referred to as ultralow frequency (ULF) waves and have been detected in magnetometer data, plasma waves, radio bursts, energetic particle bursts, and auroral far ultraviolet and X-rays (Anagnostopoulos et al, 2001;Dunn et al, 2017;Gladstone et al, 2002;Glassmeier et al, 1989;Karanikola et al, 2004;MacDowall et al, 1993;McKibben et al, 1993;Morioka et al, 2006;Nichols et al, 2017;Wilson & Dougherty, 2000); all of these have been recently reviewed by Delamere (2016).…”
Section: Introductionmentioning
confidence: 99%